(3GdCUd aj GdaQhYs - (3eMeO Hf GdMSf Hf aQbO GdTjHGfj (B( (3ehdGge (B) (3, CHh YHO Gddg , J (B189 (3g` s
(3ChdgG (B:s
(3jHJOi HGdcdGe Ydi GdeVGQHI Hbhdg (B" (3OQgekG hKdKi ajWQM efgG QCS eGd QH GdeGd s
(3BNQgG (B:s
(3jfJgi HGdcdGe Yf GdMLQ (B" (3Ke QaY Pdc Edi bGVi BNQ aCHWd efg GdMLQ (B" s
(3GdfSNI HgG MhGTs
(3LRA Yfg ecJhH ai GdbQf GdQGHYs
(3QhGjI GdEeGe CHj SdjeGf ehSi Hf SdjeGf GdLhRLGfi GdeJhai HYO SfI (B200s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B9 - (3U (B255 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B107s
Keywords: (3Gdabg GdMfajs